The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1959
DOI: 10.1302/0301-620x.41b3.507
|View full text |Cite
|
Sign up to set email alerts
|

A Method of Forefoot Reconstruction

Abstract: 1. An operation is described for the relief of irreversible claw toes associated with prominent and painful metatarsal heads. 2. The operation is suggested as an alternative to amputation of the toes. 3. The results of the operation done on twenty patients who have been followed up for a year or longer are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

1963
1963
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(32 citation statements)
references
References 0 publications
0
31
0
1
Order By: Relevance
“…), by means of resection of all MT heads, continues to be the most advocated [16]. Fowler and Clayton have modified this procedure and have more or less initiated the present-day total approach to the rheumatoid forefoot deformity underlining the importance of adequate resection of bone, usually all MT heads, with realignment of the remaining weight-bearing ends of the metatarsals [17][18][19][20]. Generally, all the lesser MT heads are resected (Fig.…”
Section: Resection Of the Mt Headsmentioning
confidence: 99%
See 2 more Smart Citations
“…), by means of resection of all MT heads, continues to be the most advocated [16]. Fowler and Clayton have modified this procedure and have more or less initiated the present-day total approach to the rheumatoid forefoot deformity underlining the importance of adequate resection of bone, usually all MT heads, with realignment of the remaining weight-bearing ends of the metatarsals [17][18][19][20]. Generally, all the lesser MT heads are resected (Fig.…”
Section: Resection Of the Mt Headsmentioning
confidence: 99%
“…Several incisional approaches have been used, including a transverse or elliptical plantar incision and a dorsal transverse incision, but currently the use of multiple dorsal incisions is the most common [17,18,20,21,24,30,38,45]. A plantar approach allows the removal of plantar calluses and bursae and offers easy access to the MT heads.…”
Section: Resection Of the Mt Headsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fowler (1959) described a patient who as a result of forefoot shortening tended to fall forwards and Barton (1973) recorded a similar case. In the latter's comparison of the techniques of Fowler (1959), Clayton (1967) and Kates et al (1967) overall instability was found to be 20%, more than twice as high as in the procedure described here. Similarly, improvement in stability occurred in fewer patients, only 40%.…”
Section: Discussionmentioning
confidence: 58%
“…The pain relief derived by these operations is almost uniformly good but the foot is shortened by one or two shoe sizes (Marmor 1975) and this is considered by many to initiate or worsen pre-existing unsteadiness (Fowler 1959, Barton 1973. The operation described here does not cause this and possesses the significant advantage that it can be performed on early cases in which the disease is localised to only two or three rays.…”
mentioning
confidence: 89%